1969
DOI: 10.1139/v69-744
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic nucleophilic substitutions. Reactions of chloro- and nitro-substituted benzenes

Abstract: The kinetics of the reaction of 2,4-dinitro-1-chlorobenzene with various aromatic bases to give 2,4-dinitrodiphenylamines have been studied in alcohol, alcohol–acetonitrile, alcohol–dimethylformamide, and alcohol – dimethyl sulfoxide mixtures. No base catalysis has been observed under these conditions. ρ Values have been computed. In the reaction of o-chloro- and p-chloronitrobenzene with hydroxide in 50% dimethyl sulfoxide, the reactivity of both the isomers has been found to be identical, in contradiction to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Methanol and ethanol, which conferred better results, are polar protic solvents, and acetonitrile is a polar aprotic solvent. Other studies have shown that the best solvents to carry out this reaction are polar aprotic solvents ; even so, this unexpected behavior for acetonitrile has previously been reported . In this case, students perform an exhaustive bibliographical revision and can suggest other solvents to include in the laboratory session.…”
Section: Resultsmentioning
confidence: 99%
“…Methanol and ethanol, which conferred better results, are polar protic solvents, and acetonitrile is a polar aprotic solvent. Other studies have shown that the best solvents to carry out this reaction are polar aprotic solvents ; even so, this unexpected behavior for acetonitrile has previously been reported . In this case, students perform an exhaustive bibliographical revision and can suggest other solvents to include in the laboratory session.…”
Section: Resultsmentioning
confidence: 99%
“…Negligible effect of mercury(II) acetate eliminates the possibility of its involvement in NBA oxidation and thus it only acts as a scavenger [14,15] for any Br − formed in the reaction and rules out the possibility of parallel oxidation by Br 2 which would have been formed by interaction of HBr and NBA [4]. + ).…”
Section: Resultsmentioning
confidence: 99%
“…KBrO 3 and NaIO 4 have been used as oxidants for glycerol [1] and cyclic alcohols [2]. Several papers have recently been devoted to the kinetics and mechanism of uncatalyzed oxidation of primary alcohols [3], dimethylsulphoxide [4], and some ketones [5,6] by Nbromoacetamide (NBA) which was earlier used as a halogenating and oxidizing agent in the estimation of several compounds [7].…”
Section: Introductionmentioning
confidence: 99%
“…Electron donoracceptor complexes in which aromatic amines function as the electron donor and other benzene derivatives function as the electron acceptor were, previously, investigated (Harold, 1976). It is well known that anilines and chlorobenzenes tend to form charge transfer complexes (Voronkov & A Y, 1965), where aniline plays the role of electron donor (Lichtfus & Zeegers-Huyskens, 1973;Radhakrishnamurti & Janardan, 1969), and chlorobenzene plays the role of electron acceptor (Dwivedi et al, 1982;Roy et al, 2018). Moreover, it is expected that a charge transfer complex CTC aniline/chlorobenzene can be formed between aniline as an electron donor (ionization potential = 7.70 eV) and chlorobenzene as an electron acceptor (electron affinity = 0.40 eV).…”
Section: Ii-formation Of a Charge Transfer Complexmentioning
confidence: 99%